Optical Brain Biopsy with a Fluorescence and Vessel Tracing Probe. Issue 4 (30th June 2021) - Richter, Johan; Haj-Hosseini, Neda; Milos, Peter; Hallbeck, Martin; Wårdell, Karin
Abstract: BACKGROUND: Accurate stereotactic biopsies of brain tumors are imperative for diagnosis and tailoring of the therapy. Repetitive needle insertions enhance risks of brain lesioning, hemorrhage, and complications due to prolonged procedure. OBJECTIVE: To investigate clinical benefits of a combined 5-aminolaevulinic acid (5-ALA) fluorescence and laser Doppler flowmetry system for the detection of malignant brain tumor and blood vessels in stereotactic biopsies. METHODS: Planning of targets and trajectories was followed by optical measurements in 20 patients, using the Leksell Stereotactic System and a manual insertion device. Fluorescence spectra, microvascular blood flow, and tissue grayness were recorded each millimeter along the paths. Biopsies were taken at preplanned positions. The diagnoses were compared with the fluorescence signals. The recordings were plotted against measurement positions and compared. Sites indicating a risk of hemorrhage were counted as well as the time for the procedures. RESULTS: Signals were recorded along 28 trajectories, and 78 biopsies were collected. The final diagnosis showed 17 glioblastomas, 2 lymphomas, and 1 astrocytoma grade III. Fluorescence was seen along 23 of the paths with 4 having the peak of 5-ALA fluorescence 3 mm or more from the precalculated target. There was increased microcirculation in 40 of 905 measured positions. The measurement time for each trajectory was 5 to 10 min. CONCLUSION: The probe provided direct feedback of increased blood flow along the trajectory and of malignant tissue in the vicinity of the target. The method can increase the precision and the safety of the biopsy procedure and reduce time.